Comparison of Geostudio and Plaxis in the Embankment dam Seepage and Slope Stability analysis: A case Study of Kundhi Dam, Oromia Ethiopia - Haimanot Shume (My University, 2025)
This study presents a comparative evaluation of seepage and slope stability analysis of the Finna Kundhi earthen dam located in Oromia Region, Ethiopia, recognizing that seepage and slope failure are major causes of embankment dam instability. The main objective of the study was to compare the performance of GeoStudio and PLAXIS software in simulating seepage behavior and slope stability under critical loading conditions. Two-dimensional numerical modeling was carried out using GeoStudio (SEEP/W and SLOPE/W) and PLAXIS based on finite element and limit equilibrium methods. Seepage and stability analyses were conducted under steadystate seepage at full supply level, end-of-construction, steady-state, and rapid drawdown conditions using available geotechnical and hydraulic data of the dam. The results showed that both software tools produced comparable seepage patterns, pore water pressure distributions, and factors of safety, with minor differences attributed to their numerical approaches. All computed factors of safety satisfied recommended international standards, indicating that the dam is stable under the considered conditions. The study recommends the use of GeoStudio for routine dam safety evaluation and PLAXIS for advanced stress–deformation analysis, together with continuous seepage monitoring to enhance long-term dam safety.
Keywords: Embankment dam; Finna Kundhi Dam; GeoStudio; PLAXIS; Seepage and slope stability